The quiet boat ride and other stories - Ruzzier, Sergio, 1966- (Ruzzier, Sergio, 1966- Fox + Chick, 2019)
Fox enjoys quiet boat rides and watching the sunrise, but Chick is noisy and hyperactive and frequently disrupts their adventures--nevertheless they remain friends and enjoy their time together.